Carboplatin and paclitaxel plus avelumab compared with carboplatin and paclitaxel in advanced or recurrent endometrial cancer (MITO END-3): a multicentre, open-label, randomised, controlled, phase 2 trial. Issue 3 (March 2023) - Pignata, Sandro; Scambia, Giovanni; Schettino, Clorinda; Arenare, Laura; Pisano, Carmela; Lombardi, Davide; De Giorgi, Ugo; Andreetta, Claudia; Cinieri, Saverio; De Angelis, Carmine; Priolo, Domenico; Casanova, Claudia; et al.
Summary: Background: Adding immunotherapy to first-line chemotherapy might improve outcomes for patients with advanced or recurrent endometrial cancer. We aimed to compare carboplatin and paclitaxel versus avelumab plus carboplatin and paclitaxel as first-line treatment with avelumab given concurrent to chemotherapy and as maintenance after the end of chemotherapy. Methods: MITO END-3 is an open-label, randomised, controlled, phase 2 trial conducted at 31 cancer institutes, hospitals, and universities in Italy. Eligible patients were aged 18 years or older with histologically confirmed advanced (FIGO stage III–IV) or recurrent endometrial cancer, an Eastern Cooperative Oncology Group (ECOG) performance status of 0–1, and no previous systemic anticancer therapy as primary treatment for advanced or metastatic disease. Participants were randomly assigned (1:1) using a computerised minimisation procedure stratified by centre, histology, and stage at study entry, to either receive carboplatin (area under the curve [AUC] 5 mg/mL × min) and paclitaxel (175 mg/m 2 ; standard group) intravenously every 3 weeks for six to eight cycles or avelumab (10 mg/kg intravenously) added to carboplatin and paclitaxel (experimental group) every 3 weeks and then every 2 weeks as a single maintenance treatment after the end of chemotherapy until disease progression or unacceptable toxicity. Patients, treating clinicians, and those assessing radiological examinations were not masked to study treatment. The primary endpoint was investigator-assessed progression-free survival, measured in the intention-to-treat (ITT) population. Patients who received at least one dose of study drug were included in the safety analysis. Experimental group superiority was tested with 80% power and one-tailed α 0·20. This trial is registered with ClinicalTrials.gov (NCT03503786 ) and EudraCT (2016–004403–31). Findings: From April 9, 2018, to May 13, 2021, 166 women were assessed for eligibility and 39 were excluded. 125 eligible patients were randomly assigned to receive carboplatin and paclitaxel (n=62) or avelumab plus carboplatin and paclitaxel (n=63) and included in the ITT population. The median follow-up was 23·3 months (IQR 13·2–29·6) and was similar between the two groups. 91 progression-free survival events were reported, with 49 events in 62 patients in the standard group and 42 events in 63 patients in the experimental group. The median progression-free survival was 9·9 months (95% CI 6·7–12·1) in the standard group and 9·6 months (7·2–17·7) in the experimental group (HR of progression or death 0·78 [60% CI 0·65–0·93]; one-tailed p=0·085). Serious adverse events were reported more frequently in the experimental group (24 vs seven events in the standard group); neutrophil count decrease was the most frequent grade 3–4 adverse event (19 [31%] of 61 patients in the experimental group vs 26 [43%] of 61 patients in the standard group). Two deaths occurred in the experimental group during treatment (one respiratory failure following severe myositis [possibly related to treatment] and one cardiac arrest [not related to treatment]). Interpretation: Adding avelumab to first-line chemotherapy deserves further testing in patients with advanced or recurrent endometrial cancer, although consideration of mismatch repair status is warranted. Funding: Pfizer.